High Keratin Secretion of T47D Cell under Hypoxic Condition - Annisa Annisa; Elizabeth Henny Herningtyas; Dewajani Purnomosari (The Prodia Education and Research Institute (PERI), 2022)
BACKGROUND: Hypoxia adaptation in cancer cells is mediated by hypoxia inducible factor (HIF)-1 that induces the expression of various proteins. Up to date, the analysis of T47D breast cancer cells-secreted protein is still limited. The aim of this study was to compare the protein profile secreted by T47D breast cancer cells under hypoxic and to normoxic conditions and identify the proteins as candidate for hypoxia marker proteins in T47D breast cancer cells.METHODS: T47D breast cancer cells were cultured under standard conditions. Cells were subcultured in normoxic and hypoxic conditions. The normoxic group was incubated with 20% oxygen and the hypoxic groups were incubated in a hypoxic chamber with 0.5% and 5% oxygen for 6, 24, and 48 hours in serum free medium. Proteins in the culture media were isolated and precipitated. Protein concentrations released by the cells were then measured by bicinchoninic assay (BCA). Protein bands were visualized by the sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) method. The bands that had differences between the hypoxic and normoxic groups were further analyzed by liquid chromatography-mass spectrophotometer (LC-MS).RESULTS: Hypoxic groups showed higher secretory protein than normoxic group. Protein bands were found in the 0.5% hypoxic group with a size of 50-75 kDa. Secretory proteins identified by LC-MS were keratin 1, 2, 9, and 10.CONCLUSION: The T47D cell line under 0.5% hypoxic treatment showed higher secretory proteins that identified as keratin 1, 2, 9, and 10.KEYWORDS: hypoxia, secretory protein, liquid chromatography-mass spectrophotometer